Putting improv to work : spontaneous performance for professional and personal life - Hohn, Greg, 1963- (Toplight, 2022)
"Improv is an art form in which participants act and respond in the present, trusting that each thoughtful action will lead to a wonderful outcome--even if it isn't the intended result. In this book, the principles and practices of unscripted theater are applied to non-theatrical circumstances. This book is based on a highly successful business school course, and aids in the development of communication, teamwork, creativity, confidence, emotional intelligence and other abilities. Each chapter assesses a different component of improv--how it connects to stage success and how it can be used in professional, academic and social settings. This is the only text that lays out an entire course on applied improv, providing activities with detailed instructions and descriptions. With roots in higher education, the book is informal, entertaining, and designed to be beneficial for anybody. Behavioral science, philosophy, art and athletics are all used to inform this discussion of improv and its real-world applications"-- Provided by publisher.
Keywords: Business communication.; Creative ability in business.; Success in business.; Interpersonal relations.; Improvisation (Acting); Success.; Achievement; Succès dans les affaires.; Succès.; Improvisation (Art dramatique); Communication dans l'entreprise.; Créativité dans les affaires.; BUSINESS & ECONOMICS / Personal Success.; Self-actualization (Psychology)